Prospective Study on Evidence Based Management of chronic Kidney Disease with Comorbidities - Habeeba, Shareefa; Fatima, Rafya; Sabah, Noor Us; Sehar, Nausheen; yousuf, Shumaila; Yezdani, Umama; Khan, Mohammad Gayoor (Asian Journal of Pharmaceutical Research and Development, 2020)
Chronic kidney disease (CKD) is a global public health problem affecting the adult population in several continents and increasing the risk of adverse outcomes. This prospective study has been conducted to understand the evidence based pharmacotherapy, Rationality of prescribed medications, Prevalence of co-occurring conditions and also to know the rate of progression of Glomerular Filtration. This research has been conducted on randomly selected inpatients (n=70) in Thumbay New Life Hospital during the months of January and February. The tools used include Informed Consent Form, Patient Counselling, Patient Medical and Laboratory Reports. Finally, the study conclude that the most common symptom of CKD is pedal edema, Most commonly occurred stage of CKD is G5, prevalence of comorbidities from High include Hypertension, Diabetes Mellitus and Coronary Artery Disease respectively. Estimated GFR has been improved in most of the patients from the duration of admission to discharge but statistical analysis shows a non-significant p value.